Utilizing the IAD index to predict ‘Rocha’ pear quality and physiological disorders after storage - Gomes, R. (2021)
In order to use the index of absorbance difference (IAD), as a fruit maturity evaluator and to assess postharvest physiological disorders, fruits from three ‘Rocha’ pear orchards (A, B, C orchards) were harvested on 8 dates during 6 weeks. At harvest, the fruits were separated into three classes of IAD (1.4-1.6, 1.6-1.8 and 1.8-2.0 or class I, II and III, respectively). One batch of fruits was stored in normal atmosphere storage (NA) for 23 weeks and the other batch in a dynamic controlled atmosphere (DCA) for 31 weeks. Standard quality parameters of the fruits were evaluated at harvest, and after 0 and 5 days of shelf life at 20°C. At 7 days of shelf life superficial scald and internal browning fruit incidence were evaluated. At harvest, the IAD index was related with firmness and ethylene production rate (r2=0.74 and 0.76, respectively) but the correlation was poor between IAD and total sugar content and fruit size (r2=0.10 and 0.45, respectively). Regarding NA storage, with the exception of orchard C, the fruits of IAD class I, for orchards A and B, 13.1% of the fruits showed superficial scald and 11.1% internal browning. The best results were from fruit of the orchard C of the IAD class III, which had 0.8 and 9.2% of superficial scald and internal browning, respectively. Considering the fruits of DCA, fruits from orchard B and of the IAD class III showed the lowest incidence of internal browning (6.2%). These results show that the orchard has a strong influence on physiological disorders and the IAD index may be insufficient to be used as the only criterion to set the harvest date and predict the level of incidence of physiological disorders